2007
DOI: 10.1590/s0100-83582007000100016
|View full text |Cite
|
Sign up to set email alerts
|

Controle de Brachiaria brizantha, com uso do glyphosate, na formação de pastagem de Tifton 85 (Cynodon spp.)

Abstract: (0; 90, 180; 360; 720; 1,080; 1,440; and 1,800

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 5 publications
2
15
0
9
Order By: Relevance
“…These results indicate that B. brizantha showed greater sensitivity to fluazifop-p-butyl, when compared with Tifton 85 plants (Figures 1 and 2), in accordance with the studies of Santos et al (2006Santos et al ( , 2007Santos et al ( and 2008 who have reported increased tolerance of Tifton 85 to glyphosate. Smeda and Putnam (1990), and Friesen & Wall (1991) also observed fluazifopp-butyl herbicide susceptibility differences between grass species.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These results indicate that B. brizantha showed greater sensitivity to fluazifop-p-butyl, when compared with Tifton 85 plants (Figures 1 and 2), in accordance with the studies of Santos et al (2006Santos et al ( , 2007Santos et al ( and 2008 who have reported increased tolerance of Tifton 85 to glyphosate. Smeda and Putnam (1990), and Friesen & Wall (1991) also observed fluazifopp-butyl herbicide susceptibility differences between grass species.…”
Section: Resultssupporting
confidence: 91%
“…When Santos et al, (2010) assessed the tolerance of Tifton 85 to glyphosate in two different application periods, they elucidated that plants exposed to this herbicide in cooler periods of the year (winter) have lower tolerance when compared with plants exposed to this herbicide in the summer. As reported by Santos et al (2006Santos et al ( , 2007Santos et al ( , 2008, Tifton 85 plants, in the summer, tend to have greater tolerance to glyphosate, possibly due to favorable conditions for growth and development, such as temperature and rooting, which may be related to the ease of metabolism, conjugation and, or, exudation of herbicides by plants, in addition to further development of starchy rhizomes, serving as reserves for regrowth of plants.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…All studies we found in the literature on weed control in pastures focused on studying the effects of herbicides on controlling unwanted plants (Silva et al 2005;Santos et al 2007;Trigueiro et al 2007). Practically no attention has been given to the study of interference relations between weeds and grasses, especially with regards to productivity and carrying capacity of the pasture.…”
Section: Introductionmentioning
confidence: 99%
“…caused the death of the forage, regardless of the application time. Urochloa brizantha, being a forage of seminiferous propagation and initially having little reserves, is more sensitive to glyphosate in the early stages of development (Santos et al, 2007).…”
Section: Brachiaria Poisoning and Growthmentioning
confidence: 99%